Urban Social Listening Potential and Pitfalls for Using Microblogging Data in Studying Cities - Hollander, Justin B.; Graves, Erin; Renski, Henry; Foster-Karim, Cara; Wiley, Andrew; Das, Dibyendu (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
XI, 97 p. 6 illus., 5 illus. in color.